2011
DOI: 10.1089/scd.2010.0453
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α Is Essential for Hypoxia-Induced Mesenchymal Stem Cell Mobilization into the Peripheral Blood

Abstract: Mobilization of mesenchymal stem cells (MSCs) is a promising strategy for tissue repair and regenerative medicine. The establishment of an appropriate animal model and clarification of the underlying mechanisms are beneficial to develop the mobilization regimens for therapeutic use. In this study, we therefore established a rat MSC mobilization model and investigated the related mechanisms, using continuous hypoxia as the mobilizing stimulus. We found that MSCs could be mobilized into peripheral blood of rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 51 publications
2
53
0
2
Order By: Relevance
“…43 Although MSC do not express VEGF receptors, 44 they produce increased amounts of VEGF in response to ischemia. [45][46][47] Indeed, MSC conditioned in GM secreted significantly higher levels of VEGF in SD/H, which was further augmented by the addition of 25 mM LPA (Fig. 5A).…”
Section: Fig 5 (A)mentioning
confidence: 88%
“…43 Although MSC do not express VEGF receptors, 44 they produce increased amounts of VEGF in response to ischemia. [45][46][47] Indeed, MSC conditioned in GM secreted significantly higher levels of VEGF in SD/H, which was further augmented by the addition of 25 mM LPA (Fig. 5A).…”
Section: Fig 5 (A)mentioning
confidence: 88%
“…41 Another common mechanism between the 2 models could involve HIF-1α as it is well established that inflammation causes a hypoxia-independent HIF-1α activation in response to the proinflammatory interleukin-1β. 42 HIF-1α regulates stem cells mobilization 43 and could therefore be involved in the recruitment of PW1 + progenitor cells. Finally, we demonstrate the presence of the PW1 + cells in the parenchyma and perivascular zones in the control human lung.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factor (HIF) is the major regulator of cellular hypoxic responses and is known to be upregulated in MSCs [68]. Furthermore, it has been reported that HIF is essential for peripheral blood MSC mobilization seen in hypoxia [69]. A deeper understanding of the activation of hypoxia response pathways in the CBF-MSCs may elucidate the mechanisms leading to the enhanced biosynthetic activity and is the subject of our ongoing investigations in this cell population.…”
Section: Discussionmentioning
confidence: 99%